INCREASING SOCIALIZATION IN ADULTS WITH ASPERGER'S SYNDROME. Issue 9 (16th September 2013) - Koegel, Lynn Kern; Ashbaugh, Kristen; Koegel, Robert L.; Detar, Whitney J.; Regester, April; Wilczynski, Susan
<x xml:space="preserve">Abstract</x> Difficulties engaging in social activities are considered to be a core symptom of individuals with autism spectrum disorder (ASD). Both the literature and our clinical observations suggest that most individuals with ASD have a desire to engage in social activities, but social skill deficits make social interaction challenging, and in turn can lead to feelings of loneliness and isolation. Currently there are few resources to support adult students with ASD in forming friendships and involvement in the college community. Using a multiple baseline design over a 33‐week period, this study evaluated the effectiveness of structured social planning for college students with ASD. Intervention included weekly sessions that included providing step‐by‐step social planning related to their interests, and feedback regarding their participation in social activities. In addition, training in specific organizational skills was implemented, such as determining activities, using a planner to ensure participation in the activities, inviting peers to activities, arranging for transportation, and so on. Results demonstrated that participants were not attending any social events throughout the baseline period. Following intervention, all participants increased the number of social events attended per week. Further, quality of life and satisfaction questionnaires all reported a higher satisfaction with their college experience and peer interactions following intervention. Finally, improvements were seen in other untargeted areas, including increases in non‐structured social interactions, improvements in grade point averages, and employment. Results are discussed in regards to a creating a social support program for college students with ASD.